Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Model Project Learning Pada Siswa Sekolah Dasar - Vizzhara, Dinda Leoni; Lubis, Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research is motivated by the low of student learning outcomes in class IV SDN 04 Garegeh. The purpose of this study was to describe the improvement of the results of integrated thematic learning using the Project Based Learning (PJBL) model in class IV SDN 04 Garegeh. The research subjects were teachers (practitioners) and 23 students. The research location is SDN 04 Garegeh. The results showed an increase in: a) observation of RPP cycle I was 91,6% (SB), cycle II 94,4% (SB); b) observation of teacher aspects of cycle I 77,77% (B), second cycle 80,55% (SB); c) observation of aspects of student cycle I 89.06% (SB) and cycle II 96.87% (SB); d) learning outcomes in the first cycle 72,2% (B ), and the second cycle 77,77% (B). Thus the Project Based learning model can improve the integrated thematic learning outcomes of IV grade 04 elementary school garegeh Students.